Natural Advantage, Location and Trade Patterns in Increasing Returns to Scale Industries - Gaetano Alfredo Minerva (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
In a two sectors, two regions economy I show that the higher increasing returns to scale of an industry, the easier it will concentrate in response to natural advantage. To this end, one sector is assumed to be perfectly competitive and the other is monopolistically competitive, with a region's firms producing at a lower marginal cost than the others in the monopolistic sector (or equivalently producing varieties more intensely demanded by consumers). If capital is mobile between regions in the long run, I analytically characterize the process of industrial location of the imperfectly competitive sector in the region with the comparative advantage.
Keywords: 330; Produktionsstandort; Monopolistischer Wettbewerb; Intraindustrieller Handel; Theorie